Adolescents’ Faith Commitments as Correlates of Their Involvement in Christian Service - Nagy, Andrea (Journal of research on Christian education, 2017)
This study sought to determine the relationship between adolescents’ involvement in service to others and their commitment to religious values and Seventh-day Adventist beliefs. Canonical correlation indicated that adolescents’ involvement in service to others is significantly related to their commitment to religious values and beliefs. Results indicated that greater commitment to religious values and Seventh-day Adventist beliefs among adolescents attending Seventh-day Adventist schools is correlated with greater involvement in service to others.